U-Pb geochronology of the Santa Cruz Formation (early Miocene) at the Río Bote and Río Santa Cruz (southernmost Patagonia, Argentina): Implications for the correlation of fossil vertebrate localities. (October 2016) - Cuitiño, José I.; Fernicola, Juan Carlos; Kohn, Matthew J.; Trayler, Robin; Naipauer, Maximiliano; Bargo, M. Susana; Kay, Richard F.; Vizcaíno, Sergio F.
Abstract: The early Miocene Santa Cruz Formation (SCF) in southern Patagonia hosts the Santacrucian South American Land Mammal Age (SALMA), whose age is known mainly from exposures along the Atlantic coast. Zircon U-Pb ages were obtained from intercalated tuffs from four inland sections of the SCF: 17.36 ± 0.63 Ma for the westernmost Río Bote locality, and 17.04 ± 0.55 Ma–16.32 ± 0.62 Ma for central Río Santa Cruz localities. All ages agree with the bounding age of underlying marine units and with equivalent strata in coastal exposures. New ages and available sedimentation rates imply time spans for each section of ∼18.2 to 17.36 Ma for Río Bote and 17.45–15.63 Ma for central Río Santa Cruz (Burdigalian). These estimates support the view that deposition of the SCF began at western localities ∼1 Ma earlier than at eastern localities, and that the central Río Santa Cruz localities expose the youngest SCF in southern Santa Cruz Province. Associated vertebrate faunas are consistent with our geochronologic synthesis, showing older (Notohippidian) taxa in western localities and younger (Santacrucian) taxa in central localities. The Notohippidian fauna (19.0–18.0 Ma) of the western localities is synchronous with Pinturan faunas (19.0–18.0 Ma), but older than Santacrucian faunas of the Río Santa Cruz (17.2–15.6 Ma) and coastal localities (18.0–16.2 Ma). The Santacrucian faunas of the central Río Santa Cruz localities temporally overlap Colloncuran (15.7 Ma), Friasian (16.5 Ma), and eastern Santacrucian faunas. Graphical abstract: Highlights: Four U-Pb ages from tuffs of the mammal-bearing Santa Cruz Formation are provided. The Santa Cruz Formation in southern Santa Cruz span from ∼18.2 to ∼15.6 Ma. Western Notohippidian and Pinturan faunas are synchronous. Notohippidian and Pinturan faunas are older than Santacrucian faunas. Santacrucian faunas may partly overlaps in time with Colloncuran and Friasian faunas.